Isolation and identification of Bacillus subtilis Withstands high concentrations of heavy metals (Journal of the College of Basic Education, 2022)
Bacterial Qualitative screening was used to get fifty five bacterial isolates from the obtained ones, all of which were undergone to bacterial quantitative screening to get two bacterial isolates. The first one which was taken from an industrial district, characterized by fast growth on Nutrient agar medium contained the minerals, Fe, Cu, Cd, Pb and Ni at concentration of 400 mg/l both individually, while the second one which was obtained from Al- Daura refinery, characterized by fast growth on Nutrient agar medium contained Ni element at the same concentration. The two isolates were identified on basis of the morphological and cultural properties, also VITEK test was done, in addition to the conduction of some complementary biochemical tests to make sure that they are Bacillus subtilis bacteria. The first isolate was named as Bacillus subtilis 1 and the second as Bacillus subtilis 2 Both isolates showed their resistance to the antibiotics Penicillin, Tetracycline, Ampcillin, Methicillin, Chloramphenicol, at concentrations of 10mcg, 10mcg, 10mcg, 5mcg, 30mcg,. both isolates showed a high ability to grow at high temperatures which included 50 to 60̊ c. consequently The maximum concentrations used for the Bacillus subtilis 1 isolate were from 800 to 2000for the minerals Cu, Zn, Pb, Ni, Fe, and Cd consequently, while the maximum concentrations used for Bacillus subtilis 2 isolate was 2000for the mineral Cr.